High incidence rate of postoperative sore throat in intubated children at Northwest Amhara Comprehensive Specialized Hospitals, Ethiopia. A multicenter study - Molla, Misganaw Terefe; Bizuneh, Yosef Belay; Nigatu, Yonas Addisu; Melesse, Debas Yaregal (Frontiers in Pediatrics, 2023)
Abstract Background: Postoperative sore throat is the most frequent complication in pediatric patients after general anesthesia. This study aimed to investigate the incidence of postoperative sore throat in patients undergoing general anesthesia with endotracheal intubation or laryngeal mask airway. Methods: A hospital-based multicenter prospective observational cohort study was conducted. Proportional allocation was done with a total of 424 patients from for four months. The information was entered into the Epi-Data software version 4.6 and analyzed with Stata 14. Socio–demographic, surgical, and anesthetic-related characteristics were analyzed using descriptive statistics. A p-value of less than 0.2 was the cutpoint of bivariate logistic regression analysis, and p-values of less than 0.05 were regarded as statistically significant in multivariate logistic regression to determine the presence and strength of association between independent variables and postoperative sore throat. Results: A total of 411 patients were included in this study, with a response rate of 96.9%. The overall proportion of patients who developed postoperative sore throat was 45 % (95% CI: 40.18–49.84). Patients who had anesthesia for more than two hours (AOR = 8.23: 95% CI = 4.08–16.5), those who were intubated by undergraduate anesthesia students (AOR = 2.67: 95% CI = 1.53–4.67), and those who had been intubated using an endotracheal tube (AOR = 2.38: 95% CI = 1.15–4.92) were significantly associated with the level of postoperative sore throat. Conclusions and recommendations: We concluded that intubated children with ETT have a high incidence of post-operative sore throat. Endotracheal tube usage, intubation by undergraduate students, and more than two hours of anesthesia duration were associated factors. The incidence of sore throat can be decreased with the use of a laryngeal mask airway, intubation by a senior anesthetist, and shortening of anesthesia time. Keywords: Children, anesthesia complications, intubation, postoperative, sore throat